Airport metal detector activation is rare after posterior spinal fusion in children with scoliosis. (December 2013) - Fabricant, Peter D.; Robles, Alex; Blanco, John S.
Purpose: Since the September 11, 2001 terrorist attacks on the World Trade Center in New York City, travel security has become an ever-increasing priority in the United States. Frequent parent and patient inquiry and recent literature reports have generated interest in the impact of heightened security measures on patients with orthopaedic implants, and have indicated increasing rates of metal detector triggering. There are no reports to date, however, evaluating children and adolescents who have undergone posterior spinal fusion for scoliosis, so responses to patient and parent inquiries are not data-driven. The purpose of this study is to determine the frequency of airport metal detector triggering by patients who have had posterior-only spinal fusion and to characterise any potential predictors of metal detector activation. Methods: A cross-sectional study was performed by interviewing 90 patients who underwent posterior-only spinal fusion for a diagnosis of juvenile or adolescent idiopathic scoliosis and have travelled by air in the past year. Demographic, clinical and surgical instrumentation data were collected and evaluated, along with patients' reports of airport metal detector triggering and subsequent screening procedures. Results: Five patients with stainless steel instrumentation (5.6 % of the cohort) triggered an airport walkthrough metal detector, and an additional five patients who did not trigger an airport detector triggered a handheld detector at a different venue. All patients who triggered an airport metal detector had stainless steel instrumentation implanted prior to 2008, and no patient with titanium instrumentation triggered any detector in any venue. All trigger events required subsequent screening procedures, even when an implant card was presented. Conclusions: In this cohort of children and adolescents with posterior spinal instrumentation, airport walkthrough metal detector triggering was a rare event. Therefore, we advise patients and families with planned posterior scoliosis fusions using titanium instrumentation that airport detection risk is essentially non-existent, and only rare for those with planned stainless steel instrumentation. We no longer issue implant cards postoperatively, as these did not prevent further screening procedures in this cohort. Level of evidence: Prognostic level 2. Study design: cross-sectional.